Identifying internet content risk for children in Sabah using GIS - Eboy, O. V; Jafar, A; Karim, H. A; Tangit, T. M; Jamru, L. R; Daud, R; Prayitno, E; Kemarau, R. A (ResearchGate, 2024)
Safety risks to children because of internet and social media use are increasing, with exposure to sexual content seen as the greatest risk. United Nations International Children's Emergency Fund (UNICEF) studies show that risks vary by country and depend on a few factors, such as children’s resilience, parental guidance, and support, as well as digital literacy (such as the ability to manage privacy settings). In Malaysia, statistical reports from government departments revealed that, sexual intercourse between unmarried young couples, being rude to parents, cyberbullying, skipping schools, smoking, drug abuse and others are becoming norms in the society. The fast development of information communication technology (ICT) was blamed for exposing negative influence on society. Therefore, this study developed an internet risk content model for children by integrating survey, statistics, and Geographic Information System (GIS). The study was based on four categories 4Cs model of online risk that can influence the children’s resillience regarding online safety which consist of content risk, contact risk, conduct risk, and contract risk. Early findings show that the internet content risk among children can relate to geographical location as most of the risk are in the same area such as Sipitang and Kudat district. This can help the authorities to focus on that area to spread awareness regarding internet usage among children.